Association between home and community-based services and depressive symptoms in Chinese older adults: a multilevel analysis - Tingke Xu; Zishuo Huang; Yucheng Huang; Shanshan Wang; Xinxin Zhang; Yaqi Hu; Yue Zhu; Dayi Cheng; Yating Fu; Xiangyang Zhang; Chun Chen (BMC, 2023)
Abstract Background As the phenomenon of ageing continues to intensify, home and community-based services (HCBSs) have been increasingly important in China. However, the association between HCBSs utilization and depressive symptoms in older adults in China is unclear. Consequently, this study aimed to examine the association between HCBSs utilization and depressive symptoms in Chinese older adults. Methods This study included 7,787 older adults (≥ 60 years old) who were recruited within the framework of the 2018 China Health and Retirement Longitudinal Study (CHARLS). Depressive symptoms were assessed using the 10-item Center for Epidemiological Studies Depression Scale (CES-D-10). HCBSs utilization was assessed via the question, "What kind of HCBSs were being utilized in their community?". Data were analyzed using binary logistic regression models and generalized hierarchical linear models (GHLM). Results Of the 7,787 participants, 20.0% (n = 1,556) reported that they utilized HCBSs, and 36.7% (n = 2,859) were evaluated that they had depressive symptoms. After adjusting for individual- and province-level covariates, the HCBSs utilization was found to be associated with depressive symptoms (OR = 1.180, 95% CI: 1.035-1.346, p < 0.05). Additionally, the depressive symptoms were significantly associated with gender, residence, educational level, marital status, number of chronic diseases, self-rated health (SRH), smoking, and provincial Gross Domestic Product (GDP) per capita. Conclusions This study found HCBSs utilization might be a protective factor against depressive symptoms in Chinese older adults. It is of utmost significance for the government to provide targeted HCBSs at the community level to address the unmet care needs of older adults, which can reduce the occurrence of negative emotions, consequently contributing to less severe depressive symptoms.